PEMBUATAN PETA SITUASI DESA BANYURIPAN KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , EDWIN WIBISANA; , Dedi Atunggal SP., ST., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report explains step by step of method, information gathering, and processing spatial data in the form of coordinates (X, Y and Z) to produce a large-scale situation map. The method used is the manufacture of map control framework which consists of Horizontal Control Surveys and Vertical Control Surveys, planimetric detail and spot height measurements, and also digital mapping. The end result is a situation map scale of 1: 500 banyuripan village Bayat subdistrict klaten district Central java province.